Model Kemitraan Contract Farming Pada Agribisnis Hortikultura ( Contract Farming Partnership model in agribusiness) - Erfit Erfit (Jurnal Embrio, 2011)
The purpose of this research is to see contract farming partnership model on horticultural agribusiness. This research using multicase method study which was combination of survey and case study. The result showed that relationship in contract farming partnership model such as : capital section, marketing and technology aid. The contract farming is a formal partnership which arranged in memorandum of understanding (MOU). The contract farming partnership benefits were 64 percent to increase farmer income, 70 percent increase technology and 68 percent increase farmer productivity.